Ways of living religion: philosophical investigations into religious experience - Gschwandtner, Christina M. (Cambridge University Press, 2024)
Ways of Living Religion provides a philosophical analysis of different types of religious experience - ascetic, liturgical, monastic, mystical, devotional, compassionate, fundamentalist - that focuses on the lived experience of religion rather than reducing it to mere statements of belief or doctrine. Using phenomenology, Christina M. Gschwandtner distinguishes between different kinds of religious experiences by examining their central characteristics and defining features, as well as showing their continuity with human experience more broadly. The book is the first philosophical examination of several of these types, thus breaking new ground in philosophical thinking about religion. It is neither a confessional treatment nor a reduction of the lived experience to psychological or sociological phenomena. While Gschwandtner's treatment focuses on Christian forms of expression of these different types, it opens the path to broader examinations of ways of living religion that might enable scholars to give a more nuanced account of their similarities and differences.